Pattern of Tobacco and Cannabis Use in a Rural Population - Solanki, Dr. Naresh; Razdan, Dr. Ram Ghulam (International Journal of Innovative Research in Medical Science, 2018)
Introduction - Various substances apart from alcohol has been using by the society since ancient times.Cannabis preparations like Bhang, Charas, Ganja and opioid preparations like afeem have been used as an aid in medication. It is one of the few studies which have included all age groups, door to door survey method, uniform diagnostic criteria and tools. Methods - This cross sectional descriptive study was conducted in 32 villages from all the four blocks of Indore district. It has covered 500 families (16 families per village) with total sample population of 2706 subjects. MINI-6 or MINI kid were administered as diagnostic tool, to all the subjects according to the age group. The study conducted during the period from December 2014 to August 2015. Results - Among 2706 people, Tobacco dependence was present as 12.7% and 1.4% in males and females respectively while tobacco use was present as 1.7% and 0.2% in males and females respectively. Cannabis dependence was present in 0.45% patients while cannabis abuse was present in 0.8% patients, all were males. Conclusion - The present study is the first study which was carried out to investigate the patterns of substance use in the given geographic settings of Madhya Pradesh. The prevalence is high among those who were low educated, those occupied in unskilled jobs like daily wage labourers, commonly in males, in the age group of 40-59 years and those who were married.